The Influence of the Corporate Social Responsibility Program on the Corporate Image of Bank Mega Syariah - Nur Wanita; Raodha Nurul Famila Koy; Noval Noval (Al-Kharaj: Journal of Islamic Economic and Business, 2022)
The purpose of this study was to examine the effect of the Corporate Social Responsibility Program on the corporate image of Bank Mega Syariah. This study uses a quantitative approach. The sample in this study were customers who received the Corporate Social Responsibility program at Bank Mega Syariah KC. Palu, which amounted to 30 people, the sampling technique used a saturated sample. Data collection techniques were carried out through observation, interviews and questionnaires. The analysis method uses simple linear regression with SPSS 23 software tools. Based on the results of the analysis, it is known that Corporate Social Responsibility has a significant and positive relationship with the Corporate Image of Bank Mega Syariah. This means that the more often Bank Mega Syariah conducts Corporate Social Responsibility programs, the company's corporate image will also be better.